1975
DOI: 10.1007/bf00385402
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium inactivation of nitrate reductase in Lemna minor L.

Abstract: The addition of ammonium to nitrate induced plants of Lemna minor L. brings about a rapid loss in extractable nitrate reductase activity. This inactivation is reversible both in vivo and in vitro. Inhibitors of RNA and protein synthesis do not protect nitrate reductase against ammonium inactivation. It is suggested that factors, in addition to ammonium ions, are components of the inactivating system. Inactivation may involve some form of protein-protein interaction. The physiological significance of rapid ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Nitrogen source may influence NRA. It has been suggested that NH 4 + may decrease NRA because of feedback inhibition from end products of NH 4 + assimilation (Orebamjo and Stewart 1975). By contrast, other studies contend that NH 4 + inhibition rarely occurs and NH 4 + is often required for optimal NRA (Mohanty and Fletcher 1976;Beevers and Hageman 1980).…”
Section: Introductionmentioning
confidence: 95%
“…Nitrogen source may influence NRA. It has been suggested that NH 4 + may decrease NRA because of feedback inhibition from end products of NH 4 + assimilation (Orebamjo and Stewart 1975). By contrast, other studies contend that NH 4 + inhibition rarely occurs and NH 4 + is often required for optimal NRA (Mohanty and Fletcher 1976;Beevers and Hageman 1980).…”
Section: Introductionmentioning
confidence: 95%
“…The higher rate of N-assimilation in the presence of NH4+ might result in an increase of this compound, compared to the situation with NO3-alone as N source (13,14). However, contradictory results have been obtained with NR from Lemna minor, which was appreciably inactivated by NH4+ within 1 h (21). Conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…The NRA in green tissues of higher plants seems to be generally unaffected or stabilized by NHI4+ (3, 19, 24) whereas a pH-dependent inhibition has been noted in roots (20,24). This pattern is, however, not universal (for Lemna, see [21]) and seems to be very much dependent on plant material, the way of culturing the plants, and the treatment ofthe plants during assay.In two accompanying papers we have presented data on the characteristics of NO3-uptake and NO3-reduction in Lemna gibba L. (12, 14). The aim of the present study was to clarify the nature of the NH4' effect on membrane NO3-transport (using '3NO3-), and to investigate the effect of NH4' on accumulation and reduction of NO3-.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…-Kaiser and Huber 2001) are affected by the relative uptake and metabolization of NO 3 − and NH 4 + (Britto and Kronzucker 2002). Indeed, NH 4 + can affect NO 3 − metabolism, because NH 4 + , or its metabolic products, can inactivate (Orebamjo and Stewart 1975a) and/ or repress NRA (Orebamjo and Stewart 1975b). The objective of this study was therefore to test whether NH 4 + can indeed inhibit the stimulation of NRA by NO 3 − in summer semi-deciduous species.…”
Section: Introductionmentioning
confidence: 98%